Sublingual Bacterial Vaccination Reduces Recurrent Infections in Patients With Autoimmune Diseases Under Immunosuppressant Treatment - Sánchez-Ramón, Silvia; Fernández-Paredes, Lidia; Saz-Leal, Paula; Diez-Rivero, Carmen M.; Ochoa-Grullón, Juliana; Morado, Concepción; Macarrón, Pilar; Martínez, Cristina; Villaverde, Virginia; de la Peña, Antonia Rodríguez; Conejero, Laura; Hernández-Llano, Keyla; et al. (Frontiers in Immunology, 2021)
Conventional or biologic disease-modifying anti-rheumatic drugs (DMARDs) are the mainstay of treatment for systemic autoimmune disease (SAD). Infectious complications are a major concern in their use. Objective To evaluate the clinical benefit of sublingual mucosal polybacterial vaccines (MV130 and MV140), used to prevent recurrent respiratory and urinary tract infections, in patients with SAD and secondary recurrent infections following conventional or biologic DMARDs. Methods An observational study in SAD patients with recurrent respiratory tract infections (RRTI) and/or recurrent urinary tract infections (RUTI) was carried out. All patients underwent mucosal (sublingual) vaccination with MV130 for RRTI or with MV140 for RUTI daily for 3 months. Clinical evaluation was assessed during 12 months of follow-up after the first dose, i.e., 3 months under treatment and 9 months once discontinued, and compared with the previous year. Results: Forty-one out of 55 patients completed 1-year follow-up. All patients were on either conventional or biologic DMARDs. A significant decrease in the frequency of RUTI (p<0.001), lower respiratory tract infections (LRTI) (p=0.009) and upper respiratory tract infections (URTI) (p=0.006) at 12-mo with respect to the previous year was observed. Antibiotic prescriptions and unscheduled medical visits decreased significantly (p<0.020) in all groups. Hospitalization rate also declined in patients with RRTI (p=0.019). The clinical benefit demonstrated was concomitant to a significant increase in both anti-S. pneumoniae IgA and IgG antibodies following MV130 vaccination. Conclusions Sublingual polybacterial vaccines prevent recurrent infections in patients with SAD under treatment with immunosuppresants therapies, supporting a broad non-specific anti-infectious effect in these patients.